2019
DOI: 10.1021/acs.jcim.9b00630
|View full text |Cite
|
Sign up to set email alerts
|

Arylamide as Potential Selective Inhibitor for Matrix Metalloproteinase 9 (MMP9): Design, Synthesis, Biological Evaluation, and Molecular Modeling

Abstract: Previous studies have reported that compounds bearing an arylamide linked to a heterocyclic planar ring have successfully inhibited the hemopexin-like domain (PEX9) of matrix metalloproteinase 9 (MMP9). PEX9 has been suggested to be more selectively targeted than MMP9’s catalytic domain in a degrading extracellular matrix under some pathologic conditions, especially in cancer. In this study, we aim to synthesize and evaluate 10 arylamide compounds as MMP9 inhibitors through an enzymatic assay as well as a cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…To determine the cytotoxicity of each extract on 4T1, T47D, and Vero cells, the MTT assay was employed. 4T1 is a triple-negative breast cancer cell line from Mus musculus [ 54 ] that contains PEX9 showing 61% homology with PDB 1ITV upon Blast Analysis [ 55 ]. T47D is a cell model to characterize the progesterone-specific effect of a luminal A subtype of breast cancer [ 56 ], whereas Vero cell is a non-tumorigenic cell from the kidney tissue of African green monkey [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…To determine the cytotoxicity of each extract on 4T1, T47D, and Vero cells, the MTT assay was employed. 4T1 is a triple-negative breast cancer cell line from Mus musculus [ 54 ] that contains PEX9 showing 61% homology with PDB 1ITV upon Blast Analysis [ 55 ]. T47D is a cell model to characterize the progesterone-specific effect of a luminal A subtype of breast cancer [ 56 ], whereas Vero cell is a non-tumorigenic cell from the kidney tissue of African green monkey [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Peptides generated to mimic the outer beta strand of blade I or IV resulted in decreased levels of MMP9 dimers and also a reduction cell migration [33]. MMP-9 can also increase angiogenesis [38]. Using an allosteric inhibitor to the PEX domain, Hariono et al [38] demonstrated that inhibition of ECM proteolysis, which decreases release of vascular endothelial growth factor (VEGF) from within the ECM, significantly reduces binding of VEGF to its membrane receptor and subsequently, decreases angiogenesis.…”
Section: Non-proteolytic Functions Of Mmpsmentioning
confidence: 99%
“…MMP-9 can also increase angiogenesis [38]. Using an allosteric inhibitor to the PEX domain, Hariono et al [38] demonstrated that inhibition of ECM proteolysis, which decreases release of vascular endothelial growth factor (VEGF) from within the ECM, significantly reduces binding of VEGF to its membrane receptor and subsequently, decreases angiogenesis. broad-spectrum compounds [42].…”
Section: Non-proteolytic Functions Of Mmpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other attempts have been made to target exosite domains, such as the HPX domain, which are less conserved. Several exosite inhibitors abrogated cancer cell migration through specific prevention of the association of pro-MMP-9 with both α4β1 integrin and CD44 without modulating the catalytic activity of MMP-9 [21][22][23]. Although exosite recognition could contribute to improving the specificity of active-site inhibitors, it remains difficult to obtain specific active-site inhibitors against a single MMP.…”
Section: Introductionmentioning
confidence: 99%